Determinants of The Policy Implementation of Guidelines Public Complaints Management in Tegal Regency Government Environment - Rezza Pamalis; Endang Larasati; Hari Susanta (Jurnal Ilmiah Ilmu Administrasi Publik, 2021)
The management of public complaints in Tegal Regency is carried out based on the Tegal Regent’s Regulation Number 10 of 2015 concerning Guidelines Public Complaints Management in Tegal Regency Government Environment. In practice, there are many complaints that come in through the available complaint channels. The problem occurs is that many complaints received indicate that there are many problems in the administration pf government in Tegal Regency, there are still unresolved problems, and the percentage of resolved problems complaints continues to decline. The purpose of this study was to determine and analyze the determinants of the policy implementation of guidelines public complaints managemen in Tegal Regency Government Environment. This study uses qualitative research methods with data analysis techniques used, namely data reduction, data display, dan drawing conclusions. The results of this study indicate that the determinant of policy implementation, namely communication is a driving factor, while resources, disposition, and bureaucratic structure are inhibiting factors.Keywords: implementation, public complaints, policy implementation